SCDevDB: A Database for Insights Into Single-Cell Gene Expression Profiles During Human Developmental Processes - Wang, Zishuai; Feng, Xikang; Li, Shuai Cheng (Frontiers in Genetics, 2019)
Single-cell RNA-seq (scRNA-seq) studies profile thousands of cells in developmental processes. Current databases for human single cell expression atlas only provide search and visualize functions for a selected gene in specific cell types or subpopulations. These databases are limited to technical properties or visualization of scRNA-seq data without considering the biological relations of their collected cell groups. Here, we developed a database to investigate single-cell gene expression profiling during different developmental pathways (SCDevDB). In this database, we collected 10 human single-cell RNA-seq datasets, split these datasets into 176 developmental cell groups and constructed 24 different developmental pathways. SCDevDB allows users to search the expression profiles of the interested genes across different developmental pathways. It also provides lists of differentially expressed genes during each developmental pathway, t-SNE maps showing the relationships between developmental stages based on these differentially expressed genes, GO and KEGG analysis results of these differentially expressed genes. This database is freely available at https://scdevdb.deepomics.org.